DESIGN AND FABRICATION OF FLUIDIZED-BED REACTOR (International Journal of Engineering and Computer Science, 2013)
A fluidized-bed reactor was designed and constructed for practical demonstration of the fluidization of solid particles at different fluid flow rates. The bed of this reactor was sand particles of average size 1800 μm ,weighed 0.6 N and the fluidizing fluidwas air. Alternatively, the fluidizing fluid can be substituted for any given gas by connecting the desired gas cylinder to the blower. The height of the bed was 25 mm on a mesh of 1230 μm. An air blower was designed to supply air from the room to fluidize the bed.The shaftand discharge powers of the blower were18.8kW and its efficiency was 70%. The minimum and maximum operating pressures were 0.1133 and 24.5262 mH2O and their corresponding velocities were 0.64 and 245.86 m/s respectively.This project was found suitable for undergraduates of Chemical Engineering and related studies for improved knowledge and practical skill required for effective and optimal performance in meeting industrial needs towards improved service delivery.